TRADE RELATIONS OF CENTRAL ASIA AND CHINA IN ANCIENT AND EARLY MIDDLE AGES (BASED ON CHINESE SOURCES) (Scientific journal of the Fergana State University, 2024)
The article presents information about trade relations between the Central Asian region and ancient Chinese dynasties based on Chinese written sources between the beginning of the 1st millennium BC and 6th century AD. In this regard, the sources were subjected to scientific analysis. The economic relations between the ancient states of Central Asia, Bactria, Parthia, Kangyu, Da-Yueji, Kushan Empire, Great Fergana (Dei-yuan), Wusun, Hun Empire and the Chinese Han, Wei, late Zhao, Northern Wei dynasties were widely covered.